Sistematização de planos de processos com auxílio de banco de dados - Freire, Nilson da Luz (2013)
This work presents a systematic methodology for the planning of database-aided processes applicable to either components of different conceptions or application sectors, looking closely to the following: technological resources, process planning activities, and the productive features in common during the manufacturing processes. All of these components always require equipment to perform the manufacturing process, of fixing device to set raw material, and tools to execute the operation. The methodology comprehends the development of a model made by three modules, which represent the method to create the process plan consisting of basic operations created and stored in compiled databases, displaying information required to the creation of process sheets. These databases belong to a network with a hierarchical structure. Such model is computerized with the development of an ACCESS application able to store the different types of information, including the ones developed in favor of each global operation. The hierarchical structures of databases successively correspond to the manufacturing procedures, the productive resources, the components, and the accessory data, which allow the elaboration of basic operations compiled in one single database. Its validation is given when some components from different manufacturing sectors are chosen, aiming to prove that process planning may be used to manufacture several components